Addressing the potential for improvement of urban building stock: A protocol applied to a Mediterranean Spanish case. (August 2021) - Blázquez, T.; Suárez, R.; Ferrari, S.; Sendra, J.J.
Highlights: Bottom-up protocol to rate urban stock energy behaviour before building upgrading. Geographic Information System ease to store and analyse building-related data. As built and upgraded energy models provide for buildings shortcomings. The protocol is applied to a Mediterranean climate-dominated Spanish city. The achieved benefits allow stakeholders in decision-making of buildings upgrading. Abstract: Current plans to combat the environmental global impact of the building sector have encouraged research on sustainable actions for increasing the renovation rate of many buildings whose performance is far from meeting current energy standards. This paper presents a protocol for analysing the existing residential stock towards planning building upgrading actions. A Geographic Information System with building-related data is used to assess the housing stock following a bottom-up approach. The urban study sample is established using several criteria at building level. The potential for improvement of buildings is ascertained using DOE 2.2 energy models which incorporate standard passive strategies to reduce the current primary energy demand and the associated CO2 emissions. The protocol is applied to the existing public housing developments built in the southern Spanish city of Córdoba, under Mediterranean conditions, during the urban expansion period which spanned 1951–1980. The extrapolation of results to the urban study sample shows a 25 % reduction in CO2 emissions and a 40 % decrease in annual energy demand. Furthermore, the impact of typology and position on the energy behaviour of a given building is acknowledged. The benefits achieved aim to help stakeholders in the implementation of energy retrofitting urban plans.